Coupling device for explosives - Jang, Hyong Doo; Yang, H.; Kim, J.; Kim, W. (2014)
A coupling device which is configured such that respective explosives for blasting work are coupled to front and rear sections thereof. The coupling device includes cylindrical bodies, one of the bodies being movable away from or close to another one of the bodies, a partition provided inside a predetermined one of the bodies to divide an inner space of the predetermined body, and an expandable support section provided between the bodies to connect the bodies to each other. The expandable support section forms a cylindrical shape together with the bodies when one body is moved away from the other body and is radially expanded when one body is moved close to the other body. The explosives can be easily inserted into a blasting hole and be positioned in the center of the blasting hole, thereby increasing the efficiency of blasting work.